Kajian Variabel Penentu Peningkatan Status Jalan Nasional di Lintas Selatan Jawa Barat - Fachrie, Noor; Rudiarto, Iwan (Magister Pembangunan Wilayah dan Kota,Undip, 2016)
The Indonesian archipelago that stretches from Sabang( Sumatra Islands ) to Merauke ( Papua Islands ) has a variety of abundant natural resources , one of which are West Java Province . Central Government through the Ministry of Public Works â€“ Public Housing has allocated Rp 1 trillion in APBN 2013 (presidential directive allocation) for the road construction of south traffic in West Java. This thesis aims to assess the effect / assessment of variables (i) land use - transportation; (ii) the pattern of development of the area and the road network system; (iii) spatial and regions; and (iv) the level of transport in the National Transportation System (SISTRANAS) towards improving the status of south traffic road of West Java to be became a national road in perspective the function of the road network, which is expected to provide an objective assessment in evaluating the proposed of roads status improvement. Positivistic and rationalistic approach used in this study to design variables and criteria for assessment of land use; the pattern of development of the area and the road network system; spatial and regions; as well as the transport level in the National Transportation System (SISTRANAS). Quantitative descriptive method in this research is intended to provide a description / overview and assessment of data analysis in the form of numbers. The research concludes that the variable of land use - transport and national transportation system (Sistranas) variable can be taken into consideration, because these two variables more realistic in assessing improvement the status and function of the national road compared to the other variables.Â